Investigation of InGaAs/InP photodiode surface passivation using epitaxial regrowth of InP via photoluminescence and photocurrent. (February 2023) - Braga, O.M.; Delfino, C.A.; Kawabata, R.M.S.; Pinto, L.D.; Vieira, G.S.; Pires, M.P.; Souza, P.L.; Marega, E.; Carlin, J.A.; Krishna, S.
Abstract: The viability of epitaxial regrowth of InP to passivate lateral mesa surfaces of lattice-matched InGaAs/InP photodiodes is investigated. The effect of the passivation is quantified via a proposed method that uses multiwavelength photoluminescence to determine the surface recombination velocity (SRV). The effective minority charge lateral diffusion length is also obtained using photocurrent measurements with flood illumination. We propose a methodology where this data can be used together with the SRV to estimate the absorber layer minority charge lifetime. A surface recombination velocity of ( 3.7 ± 0.1 ) × 1 0 4 cms −1 was found for the InGaAs/regrown InP interface, which represents a reduction of 2 orders of magnitude when compared to the value of ( 6.3 ± 0.1 ) × 1 0 6 cms −1 obtained for an unpassivated InGaAs surface. Highlights: Quantification of improvements due to passivation with regrowth of InP on InGaAs. Methodology for determining the surface recombination velocity (SRV). Alternative methodology for determining the bulk lifetime in photodiodes active layer. Strong reduction in surface recombination velocity (SRV). Obtained SRV value not found in the literature for InP regrown on NID InGaAs.